2007
DOI: 10.1007/s00223-007-9040-2
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Immunosuppressive Monotherapy from Cyclosporin A to Tacrolimus Reverses Bone Loss in Rats

Abstract: Tacrolimus is used for transplant patients with refractory graft rejection and those with intolerance to cyclosporin (CsA), without the disfiguring adverse effects frequently attributed to CsA therapy. Since we have shown that CsA-associated bone loss can also affect alveolar bone, the purpose of this study was to evaluate the effects of conversion of monotherapy from CsA to tacrolimus on alveolar bone loss in rats. Groups of rats were treated with either CsA (10 mg/kg/day, s.c.), tacrolimus (1 mg/kg/day, s.c.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
17
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 53 publications
7
17
4
Order By: Relevance
“…According to these authors, this dose would be equivalent to 3.2 mg/kg orally, which is the dose we employed in the present work. Spolidorio et al (2007) found an increase in the resorption marker FATR following administration of CsA (a finding we did not reach with the CTX/TRAP marker) in rats treated with 10 mg/kg/day of CsA (a dose 5 times higher than ours). Another important point is that these authors used 50 g rats, many of which were younger than ours, a fact which could have caused the different effects of immunosuppressants on bone remodeling.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…According to these authors, this dose would be equivalent to 3.2 mg/kg orally, which is the dose we employed in the present work. Spolidorio et al (2007) found an increase in the resorption marker FATR following administration of CsA (a finding we did not reach with the CTX/TRAP marker) in rats treated with 10 mg/kg/day of CsA (a dose 5 times higher than ours). Another important point is that these authors used 50 g rats, many of which were younger than ours, a fact which could have caused the different effects of immunosuppressants on bone remodeling.…”
Section: Discussioncontrasting
confidence: 89%
“…Folwarczna et al (2009) administering a low dose of FK-506 (0.3 mg/kg/day) to adult male rats, found that this dose increased bone formation. Results that differed from ours were found by Spolidorio et al (2007). These authors administered 10 mg/kg/day of CsA subcutaneously to one group of rats and 1 mg/kg/day of FK-506 to another group.…”
Section: Discussioncontrasting
confidence: 73%
“…A significant decrease in serum calcium level in the Cs-A treated group which was statistically significant when compared to the other groups was observed in our study. These findings are in concordance with previous studies 10,33,34 who suggested that the decreased levels of serum calcium can be attributed to the non specific effect of cyclosporin-A due to increased excretion by kidney and/or increased bone uptake. Cs-A has also shown to induce a change in the calcium flux via cellular membrane permeability.…”
Section: Alveolar Bone Loss:-supporting
confidence: 83%
“…A great quantity of osteocytes indicates bone maturity [38]. The increase in the quantity of osteoclasts is associated with bone resorption [39]. The present research found a high quantity of mandibular alveolar bone osteocytes in all the groups and a small quantity of osteoclasts, but no significant difference was found among the groups, which indicates that neither MSGinduced obesity nor bariatric surgery significantly caused changes in the number of bone cells.…”
Section: Discussionmentioning
confidence: 48%